2011
DOI: 10.1186/1476-0711-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and resistance-modifying activities of thymoquinone against oral pathogens

Abstract: BackgroundThe presence of resistant bacteria in the oral cavity can be the major cause of dental antibiotic prophylaxis failure. Multidrug efflux has been described for many organisms, including bacteria and fungi as part of their drugs resistance strategy. The discovery of a new efflux pump inhibitor could extend the useful lifetime of some antibiotics.MethodsIn this study, the MICs of thymoquinone (TQ), tetracycline and benzalkonium chloride (BC) were determined in absence and in presence of a sub-MIC doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…These results support previous studies which reported an effective antibacterial activity of N. sativa essential oil (22), thymoquinone (23) and carvacrol (24) against Gram-positive bacteria. DMSO and EtOH as diluents did not show any inhibitory effect on the growth of the strains.…”
Section: Discussionsupporting
confidence: 92%
“…These results support previous studies which reported an effective antibacterial activity of N. sativa essential oil (22), thymoquinone (23) and carvacrol (24) against Gram-positive bacteria. DMSO and EtOH as diluents did not show any inhibitory effect on the growth of the strains.…”
Section: Discussionsupporting
confidence: 92%
“…20,[23][24][25][26][27] Furthermore, the antibacterial activity of N. sativa seed extract and its constituents against some strains of Streptococcus associated with dental caries has been reported as well. 14,28 Consistent to the results of previous studies, the present study demonstrated a strong growth inhibition and bactericidal activity of DLBS1355 o/w emulsion against S. mutans and S. sanguis, with a slightly higher activity on S. sanguis.…”
Section: Discussionsupporting
confidence: 92%
“…The antibacterial effect synergism of N. sativa seed essential oil with antibiotic was reported in several previous studies, therefore it may be used in combination with antibiotic. 28,46 Further investigation is needed in order to investigate the cytotoxic effect of N. sativa seed o/w emulsion regarding to human use.…”
Section: Discussionmentioning
confidence: 99%
“…This compound is a phyto-quinone present only in the EO of N. sativa. One of the most important antimicrobial characteristics of TQ is its ability to modify the resistance of bacteria to antibiotics by acting as efflux pump inhibitor 30 . Efflux pumps are proteins in the cell membrane of the bacteria that extrude the antimicrobial agents outside the cell 31 .…”
Section: Antimicrobial Evaluationmentioning
confidence: 99%